Sensitive and critical periods in visual sensory deprivation - Voss, Patrice (Frontiers in Psychology, 2013)
While the demonstration of crossmodal plasticity is well established in congenital and early blind individuals, great debate still surrounds whether those who acquire blindness later in life can also benefit from such compensatory changes. Yet no proper consensus has been reached despite the fact that a proper understanding of the developmental time course of these changes, and whether their occurrence is limited to - or within - specific time windows, is crucial to our understanding of the crossmodal phenomena. An extensive review of the literature reveals that while the majority of investigations to date have examined the crossmodal plasticity available to late blind individuals in quantitative terms, recent findings rather suggest that this reorganization also likely changes qualitatively compared to what is observed in early blindness. This obviously could have significant repercussions not only for the training and rehabilitation of blind individuals, but for the development of appropriate neuroprostheses designed to aid and potentially restore vision these same individuals. Important parallels will also be drawn with the current state of research on deafness, which is particularly relevant given the recent advances in the development of successful neuroprostheses (e.g. cochlear implants) for providing auditory input into the central nervous system otherwise aurally deafferented. Lastly, this paper will address important inconsistencies across the literature concerning the definition of distinct blind groups based on the age of blindness onset, and propose several alternatives for future investigations.